2022
DOI: 10.1186/s12890-022-02149-x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of cost-utility analyses of screening methods in latent tuberculosis infection in high-risk populations

Abstract: Background The World Health Organisation (WHO) recommends that testing and treatment for latent tuberculosis infection (LTBI) should be undertaken in high-risk groups using either interferon gamma release assays (IGRAs) or a tuberculin skin test (TST). As IGRAs are more expensive than TST, an assessment of the cost-effectiveness of IGRAs can guide decision makers on the most appropriate choice of test for different high-risk populations. This current review aimed to provide the most up to date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
(184 reference statements)
0
9
0
Order By: Relevance
“…The assessment of cost-effectiveness for TBI screening among migrants is affected by the TBI prevalence found in the screened population [ 29 ]. In our study, screening was offered to all migrants who recently arrived, asylum seekers or undocumented, regardless of incidence in the country of origin, resulting in around 30% of our population coming from countries with TB incidence <150/100,000.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of cost-effectiveness for TBI screening among migrants is affected by the TBI prevalence found in the screened population [ 29 ]. In our study, screening was offered to all migrants who recently arrived, asylum seekers or undocumented, regardless of incidence in the country of origin, resulting in around 30% of our population coming from countries with TB incidence <150/100,000.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of cost–utility analyses of LTBI screening tests specifically focused on high-risk populations, concluding that the economic evidence is robust enough to draw conclusions only for high-income and low-TB-burden countries, with limited evidence from high-TB-burden countries [ 10 ]. This systematic review also concluded that cost effectiveness varies depending on the LTBI prevalence or population tested; among low-risk populations, as well as children without any other LTBI or TB risk factors Screening with TST or no LTBI testing at all is often the most cost effective strategy compared to screening with IGRAs [ 7 , 10 ], reinforcing that LTBI screening should be carefully considered in low-TB-burden settings and only implemented for targeted high-risk groups who have increased risk of exposure and/or increased risk of progression to TB.…”
Section: Ltbi Screeningmentioning
confidence: 99%
“…For example, the rate of progression to active TB has been shown to have an important impact on the cost effectiveness of LTBI interventions, meaning that the cost effectiveness of screening and TPT varies widely across different subpopulations with different risks of active TB progression. While implementation considerations may be more critical in ensuring the cost effectiveness of screening and TPT in the general population, economic evaluations have been highly consistent in demonstrating that screening and prevention programs for TB are highly cost effective when targeted towards contacts with recent TB exposure and PLHIV [ 4 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, most costing studies comparing TB diagnostics ignore the opportunity cost—the cost of opportunity forgone, or the potential benefit that would have been incurred should the alternative been chosen—in their calculations, particularly in high-burden, low-income settings 17. For example, cost analyses of TB diagnostics measure patients’ lost income due to diagnosis but do not incorporate benefit to society in the form of reduced transmission 18 19.…”
Section: Introductionmentioning
confidence: 99%